Implementation Of Islamic Philantropy On Ownership Of Securities At The Indonesia Stock Exchange In West Nusa Tenggara Province - Hasanah, Ulfatun; Susianti, Nurul; Awwalunnisa, Nur; Darmayani, Dania (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
Stock zakat in Indonesia holds significant potential to support socio-economic development; however, it still faces several challenges, particularly in terms of financial literacy and investor participation. Data shows that only around 10% of investors are aware of their zakat obligations on stock ownership, despite the increasing number of investors annually. This study focuses on the implementation of Islamic philanthropy, specifically stock zakat, at the Indonesia Stock Exchange (IDX) West Nusa Tenggara branch in collaboration with BAZNAS NTB and BAZNAS Mataram city. Data collection methods include observation between, and documentation. The findings indicate that collaboration between financial institutions and zakat organizations can enhance the transparency and accountability of stock zakat distribution. Therefore, the potential of stock zakat can be optimized to support inclusive and sustainable regional economic growth. Keywords: Stock Zakat, Philanthropy, Sharia Capital Market, BAZNAS, Indonesia Stock Exchange.